XI International Conference on Structural Dynamics 2020
DOI: 10.47964/1120.9338.19599
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Absorption Performance of Metamaterial Lattices Consisting of Impact Dampers

Abstract: In recent years, metamaterials are increasingly used in the field of vibration mitigation due to the unique potential these offer. Periodic placement of appropriately designed resonators, the so-called unit cells, has been shown to arrest the propagation of vibration within a specific frequency range, thus resulting in formation of a bandgap. In rendering metastructures efficient, the breadth of the bandgap should be maximized, while for application in structures, it is also necessary to shift the lower limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The study considered variable parameters, such as the number of unit cells, stiffness, and mass ratio. Their findings demonstrated that the proposed method significantly impacts the base meta structure, leading to effective vibration mitigation9 . Lv et al (2024) proposed a metamaterial based on Coulomb friction is self-recoverable and reusable.…”
mentioning
confidence: 99%
“…The study considered variable parameters, such as the number of unit cells, stiffness, and mass ratio. Their findings demonstrated that the proposed method significantly impacts the base meta structure, leading to effective vibration mitigation9 . Lv et al (2024) proposed a metamaterial based on Coulomb friction is self-recoverable and reusable.…”
mentioning
confidence: 99%